The Relationship of Visits to Posyandu with the Nutrition Status of Toddlers in Amplas Health Center - Namora Lumongga; Etti Sudaryati; Donna Theresia (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
Weighing the child's weight every month to find out the nutritional status of children is one of the routine activities at the Posyandu. One effort to reduce the problem of malnutrition in children is to increase the participation of mothers in visiting and weighing their children to the Posyandu every month. This study aims to determine the relationship of the number of Posyandu visits with the nutritional status of children under five (1-5 years). This study uses a descriptive correlation design with a retrospective approach. The study was conducted in the working area of the Amplas Health Center with a sample of 382 mothers and children under five years old using proportional random sampling technique based on the number of Posyandu. The measuring instrument used was a questionnaire for demographic data and a child's weight-weighing registration book. The analysis used is univariate analysis to determine the frequency distribution and bivariate analysis using chi-square. The results showed that 145 people (38%) regularly visited Posyandu and 237 people (62%) did not regularly visit Posyandu. Children who have good nutritional status are 203 people (53.1%), malnutrition is 109 people (28.5%), and malnutrition is 70 people (18.3%). The bivariate analysis results obtained p value (0.00) <ɑ (0.05), so it can be concluded that there is a correlation between the number of Posyandu visits and the nutritional status of children under five. Suggestions for puskesmas staff to be able to conduct training and health education to cadres and improve health facilities in Posyandu.